Kerugian Ekonomi Akibat Penyakit Rabies di Provinsi Bali (ECONOMIC LOSSES OF RABIES IN BALI) - Batan, I Wayan; Lestyorini, Yunita; Milfa, Sri; Iffandi, Calvin; Nasution, Abdul Azis; Faiziah, Nurul; ., Rasdiyanah; ., Herbert; Palgunadi, Ni Wayan Listyawati; Suatha, I Ketut; Kardena, I Made (Jurnal Veteriner, 2015)
The purposeof this studywas toanalyze theeconomic losses due torabies outbreak on human anddogin the province ofBali in2008-2011. The data usedin this research wereobtainedfrom the DepartmentofHealth, Department of Animal Husbandryand Animal Healthin district level, and theprovince ofBali,Disease of Investigation Centre of Denpasar, mass media(BaliPost), as well asinterviews withtheallegedvictims of dogbiterabies. The data wereanalyzed usingeconomic models.The results showedthatthetotaleconomic loss(TK) due toan outbreakof rabiesinBali in2008-2011amounted toRp336,509,892,200.Economic lossesdue torabiesin Bali provincewere mainly frompublic health costs(KM) and the costofvaccinationandelimination(BVE) dogs. Public health costs(KM) spent the greatest loss of moneyin 2010.However, costof dogvaccination andcullingwere spent at highestin 2011. Total of economic losses(the highestlosses)(TK) of the diseasein the province ofBalioccurredin 2011, whilethe lowestin 2008.Publicawarenessfortied and cage pet is urgently needed toreduce thenumber of rabiescases. Decreasenumber of dog bites may result in reducing the related economic losses.
Keywords: economic losses, rabies in Bali